Academic Casualization, Precarity, and Information Practices: A Scoping Review. Issue 1 (14th October 2022) - Willson, Rebekah; Stewart‐Robertson, Owen; Julien, Heidi; Given, Lisa
ABSTRACT: In the first phase of a larger research project exploring the information practices of contract academic staff, a review of the wider literature around academic casualization was conducted. This research begins to address the need for greater understanding of the experiences of these workers in the information‐intensive environments of higher education. A scoping review methodology was applied, and both academic and grey literature from multiple disciplines was reviewed. The literature points to casualization in academia as a growing phenomenon that has important consequences for staff, students, and universities themselves. This poster discusses the initial themes emerging from the literature, including: the precarity and marginalization of academic staff, the unrecognized emotional labor shaping information practices, and the impacts of multiple temporalities on the work, careers, and lives of such staff. The findings suggest the need for empirical research to address the lack of knowledge around the information environments of contract academics and set the stage for the next phases of the research project.